Looted art & restitution : the exodus and partial return of Dutch art poperty during and after World War II - Ekkart, Rudolf E. O. (Waanders Publishers, 2023)
"Looted Art & Restitution relates the history of the trade, looting and restitution of works of art from the Netherlands before, during and after World War II. Due to the German collection rage, countless artworks ended up in German hands during the occupation. The allies recovered a large number of works of art to the Netherlands after the war. It was the Dutch government's task to return looted or forcibly sold works to their original owners. The mostly Jewish claimants, however, often encountered bureaucratic and unwilling authorities. Meanwhile, most of the artworks were distributed over museums and depots or auctioned off. It was not until the late 1990s that, in accordance with international developments, the restitution policy became much more humane and a search for the rightful owners was implemented."--Page 4 of cover